Pengembangan Produk Minuman dari Daging Buah Manggis (Garcinia mangostana L.) Beku - Nuri Andarwulan; Fadhilah Nur’Azizah; Sutrisno Koswara (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
Mangosteen peel extract is manufactured as nutraceutical with high antioxidant properties. The industry does not process the flesh of the mangosteen fruit yet. The aim of this research was to study the formulation of ready to drink (RTD) mangosteen fruit juice and the stability of its product during storage. The RTD was processed with a hot fill protocol. The organoleptic liking rate of three fruit juice formulas was 5.36 to 5.74 on a scale of 7. The selected formula consisted of fruit pulp and water in the ratio of 1:2.33 or 300:700 g, sugar 70 g, dark red synthetic colorant 0.0680 g, artificial mangosteen flavoring 2.0 g, CMC 0.25 g, ascorbic acid 0.25 g, and sodium benzoate 0.10 gin the total weight of the mangosteen fruit juice of 1 000 g. The physicochemical characteristics (pH, viscosity and total soluble solid) of mangosteen fruit juice decreased during storage. The microbiological characteristic of raw mangosteen pulp and its RTD complied with BSN standard (2014) for fruit juice products.